2018
DOI: 10.1007/s00420-018-1326-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in a cohort of asbestos-exposed workers undergoing health surveillance

Abstract: This cohort experienced an excess in the incidence of both mesothelioma and lung cancer, showing increasing incidence rates at higher level of asbestos exposure. For lung cancer, the relative incidence was highest among workers hired in shipbuilding between 1974 and 1984.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
5
5
2
Order By: Relevance
“…A higher mortality risk of 1.68 (95% CI: 1.19–2.30) was found in the Polish cohort of workers compensated for asbestosis, 19 and in two Italian cohorts 16,17 . The SIR of 1.61 (95% CI: 1.26–2.04) in one of the Italian cohorts was slightly higher than our risk estimate 15 . In our previous German surveillance cohort study we observed a decreased lung cancer mortality of 0.39 (95% CI: 0.17–0.77) 12 .…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…A higher mortality risk of 1.68 (95% CI: 1.19–2.30) was found in the Polish cohort of workers compensated for asbestosis, 19 and in two Italian cohorts 16,17 . The SIR of 1.61 (95% CI: 1.26–2.04) in one of the Italian cohorts was slightly higher than our risk estimate 15 . In our previous German surveillance cohort study we observed a decreased lung cancer mortality of 0.39 (95% CI: 0.17–0.77) 12 .…”
Section: Discussioncontrasting
confidence: 82%
“…For lung cancer we observed a much lower SIR of 1.27 than for mesothelioma. A higher mortality risk of 1.68 (95% CI: 1.19–2.30) was found in the Polish cohort of workers compensated for asbestosis, 19 and in two Italian cohorts 16,17 . The SIR of 1.61 (95% CI: 1.26–2.04) in one of the Italian cohorts was slightly higher than our risk estimate 15 .…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…A more prominent magnitude of relative risk of male gastric cancer, with SMR = 1.91 (95% CI 1.03–3.56), can be noted in the subgroup sample of occupational cohorts in China and Russia. Barbiero et al reported a borderline increased incidence found for gastric cancer (SIR = 1.53, 95% CI 0.96–2.31) in an Italian cohort enrolled in a public health surveillance program [ 24 ]. A case of gastric cancer was recognized as work-related disease in a 57-year-old Korean man who had continuous exposure to high levels of asbestos for 40 years [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found relatively lower ratios of LC to MPM deaths and incidence: about 3 to 1 and 2 to 1, respectively. 10,11 Applying the same proportions to Monfalcone shipyard workers would lead to crude estimates of between 340 and 680 expected LC cases. If the above assumptions hold, only about 20% to 40% of all LC cases have been reported to the public prosecution office and have undergone autopsy, reducing considerably the size and power of our study and creating the potential for selection of the included cases.…”
Section: Discussionmentioning
confidence: 99%